2022
DOI: 10.1101/2022.02.03.22269612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biologic correlates of beneficial convalescent plasma therapy in a COVID-19 patient reveal disease resolution mechanisms

Abstract: BackgroundWhile the biomarkers of COVID-19 severity have been thoroughly investigated, the key biological dynamics associated with COVID-19 resolution are still insufficiently understood.Main bodyWe report a case of full resolution of severe COVID-19 due to convalescent plasma transfusion in a patient with underlying multiple autoimmune syndrome. Following transfusion, the patient showed fever remission, improved respiratory status, and rapidly decreased viral burden in respiratory fluids and SARS-CoV-2 RNAemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…For these exploratory analyses, 13 uncontrolled large case series without individual patient data enrolling 358 participants were included in descriptive analysis . In this study, 125 case reports or case series enrolling 265 participants were included for patient-level exploratory analyses. One study was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“…For these exploratory analyses, 13 uncontrolled large case series without individual patient data enrolling 358 participants were included in descriptive analysis . In this study, 125 case reports or case series enrolling 265 participants were included for patient-level exploratory analyses. One study was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“… Along with the delay of CP administration day, the length of stay in the ICU grew. Natalie Bruiners et al 139 Beneficial CPT in a patient with COVID-19 revealed disease-resolution pathways by its biological correlates (CR) Hydroxychloroquine, methotrexate, rituximab infusion, azithromycin 4-litter supplemental O 2 Day 40: 400 mL of COVID-19 CCP from an unidentifiable donor The patient was given 600 mL of her relative’s CP on day 54. On day 54, the patient’s O 2 saturation increased to the point where supplemental O 2 was no longer needed.…”
Section: Introductionmentioning
confidence: 99%